2011
DOI: 10.1111/j.1741-4520.2011.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of drug treatments in pregnant women with the risk of external ear congenital abnormalities in their offspring: A population-based case-control study

Abstract: The objective of this study was to evaluate the possible association of drug treatments in pregnant women with a higher risk of congenital abnormalities of the external ear, particularly microtia/anotia, in their children. The frequency of drug treatments was compared in the mothers of cases with isolated or multiple (syndromic) ear abnormalities and in the mothers of three different controls: controls matched to cases, all controls (these controls had no defects) and malformed controls in the population-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…These possible triggering factors such as maternal diseases (e.g. diabetes mellitus) and drugs (antiepileptic medicines) were detected in the origin of IMA in our previous studies [2,3]. Table 3 The objective of the study was to test the multifactorial etiology of cases with IMA based on the comparison of observed and expected numbers of affected first degree relatives with IMA, and there was no significant difference between expected and observed total numbers of first degree relatives with IMA (p = 0.47).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These possible triggering factors such as maternal diseases (e.g. diabetes mellitus) and drugs (antiepileptic medicines) were detected in the origin of IMA in our previous studies [2,3]. Table 3 The objective of the study was to test the multifactorial etiology of cases with IMA based on the comparison of observed and expected numbers of affected first degree relatives with IMA, and there was no significant difference between expected and observed total numbers of first degree relatives with IMA (p = 0.47).…”
Section: Discussionmentioning
confidence: 93%
“…congenital abnormalities (CAs) of external ears. Previously the possible environmental factors such as maternal socio-demographic features [1], diseases [2] and related drug treatments [3] were evaluated in these cases. The objective of this study is the analysis of the possible genetic origin of isolated microtia/anotia on the basis of their familial cluster.…”
Section: Introductionmentioning
confidence: 99%
“…Working with the hypothesis that phenytoin could be effective by limiting deleterious effects of intrapartum asphyxia, Lampley et al (1995) pre‐treatment of guinea pigs dams with phenytoin before hypoxia (7% O 2 , for 60 min) exposure and observed that the injury decreased Na + , K + ‐ATPase activity and increased lipoperoxidation; reversed by phenytoin pretreatment (Lampley et al, 1995). Although interesting for its capability in preventing early events of HI cascade in preclinical settings, we did not find additional reports using phenytoin in HI context, possibly due to its side effects such as hypotension, coagulation problems (Baxter et al, 2004) and increased risk for fetal abnormalities observed in the clinic (Paput et al, 2011).…”
Section: Pharmacological Agentsmentioning
confidence: 80%
“…Although several published reports have attempted to identify risk factors for microtia, only four of these have been case–control studies (Table ) (Castilla and Orioli, ; Mastroiacovo et al, ; Paput et al, ; Van Bennekom et al, ). While they also recruited controls through population and hospital birth cohorts, these ranged in size from 172 to 411 cases, and control participation rates were reported for only one study (Van Bennekom et al, ) retaining the possibility that bias may have accounted for some of the associations which were reported.…”
Section: Discussionmentioning
confidence: 99%